KONSEKUENSI TEKNOLOGI KOMUNIKASI COMPUTER MEDIATED COMMUNICATION PADA APLIKASI TA’ARUF ONLINE - Elysia, Eda; Delpa, Delpa; Khairyah, Miftahul (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
Muzmatch.com is one of the modern applications for Muslims around the world. The presence of this application is a new alternative for finding a life partner (mate). A modern application that uses Artificial Intelligence (AI) and no longer recognizes distance, space, and time. Muzmatch.com connects couples between countries which makes cross-border marriages so common today. The application system that has started to apply artificial technological sophistication allows couples to have direct communication access without any intermediaries. This shift is a consequence of communication technology where with the presence of the internet, each individual can find a partner through the virtual world. Research with qualitative methods using a phenomenological approach is more focused on exploring the experiences of informants who use the Muzmatch.com application and the role of the Muzmatch.com application system. This study aims to analyze the ta'aruf process through the Muzmatch.com application and the role of the systemized features in the Muzmatch.com application. The informants of this study consisted of two people who used the online application Muzmatch.com, who were selected using a purposive sampling technique, especially in the city of Padang. The results of this study showed that the stages that were passed by the informants who used the muzmatch.com application, among others: register (register), swipe up, automatically saved data, chat via messenger.